Molluscum Contagiosum in Baquba City Epidimiological Study with Identification of Mc Viruses by Polymeras Chain Reaction - Al-Kayalli, Khudhair Khalf; Ahmed, Raghad Ibrahim; Irzuqy, Brooj Mohammad; Husain, Wathek Mohammed (Diyala Journal of Medicine, 2019)
Background: Molluscum contagiosum is a DNA virus, which may infect the mucous membrane, it is caused by Molluscipox virus and there are four types (MCV1-4). The sites of predilection of lesions are the face and neck, both genders equally affected and most commonly seen in childhood age group. Objectives: To study the epidemiological variables of Molluscum contagiosum and to confirm the clinical diagnosis and type of Molluscum cotagiosum virus (MCV) by Polymerase chain reaction (PCR) technique. Patients and methods: The present study was conducted for the period from 1st November 2011 to 30th April 2012 in outpatient clinic of Baquba teaching hospital in Baquba city. One hundred and sixty two patients with molluscum contagiosum were examined and diagnosed clinically and the diagnosis was confirmed by Polymerase chain reaction technique .The lesions of moluscum contagiosum were seen on different sites of the body, age of patients ranged from (1-80 years) with a mean age of 35+_9years . They were 114(70.6%) males and 48(29.4%) females. Results: The results showed that 72 (44.4%) patients of age group (31-40 years), of which 50 (70%) were males and 22 (30%) females, 35 (21.6%) of age group (ten years or less). This study revealed that 56(35%) of patients were illiterate, without statistical significant difference between MC infection and educational levels. In 78% of patients the lesions located on the head and neck, 70% on the right side and in 78% of patients the number of lesions was ≤10 lesions, 70% of patients lived in the urban areas and 30% in rural areas. Eighty five percent (85%) of patients give positive results for MCV, 58.8% of them shows positive results for MCV type 1 and 2 (73.3% MCV-2 and 26.7% MCV-1), while 41.2% shows negative results . Conclusion: We concluded that Molluscum contagiosum was a disease of adult, predominantly males and on the right side of the face and 73.3% of PCR positive results were MCV-2.